Javanese Cultural Inculturation in the Depiction of Mother Mary’s Statues: a Semiotic Analysis and Theological Reflection - Patrik Diego Arbi Arwendi; Yohannes Bramanda Ryan Kharisma; Feremenatos Oktafilio Adi Prasetya (Proceedings of The International Conference on Theology, Religion, Culture, and Humanities, 2024)
Inculturation is one of the crucial aspects in the living out of the Christian faith. Without inculturation, the Christian faith would become alienated from the context of believers’ lives. Conversely, with inculturation, faith becomes more vibrant as it is not only expressed in accordance with the local context, but also touches the concrete lives of the people. This research concentrates in exploring the uniqueness and distinctiveness of the inculturation of four statues of Mother Mary within Javanese culture in several pilgrimage sites and churches. The four statues of Mother Mary are Dyah Marijah Iboe Ganjoeran, Maria Ratuning Katentreman lan Karaharjan in Gantang, Bunda Maria Stella Maris in Pacitan, and Maria Bunda Segala Suku in Jakarta. By using this qualitative method, the research employs literature review, interviews, and field observations. The aim of this research is to analyze the forms of Javanese-styled Mother Mary statues and reflect on them within the framework of theological inculturation. Based on Ferdinand de Saussure's semiotic analysis, it is concluded that the Mother Mary statues are signs that representing her personality. As sign, each statue has symbolic meanings derived from its name/title, accessories, clothing, and body position. The theological reflection also indicates that each statue possesses dimensions of inculturation that align with the local (Javanese) cultural taste. Therefore, the acculturative effort towards these Mother Mary statues further supports the devotion of the faithful to the figure of Mother Mary, as one of the expressions of their faith.